方程-x2-3=-56+1-x3移项,得( )
举一反三
- 方程-x2-3=-56+1-x3移项,得( ) A: 1-x3-x2=-3+56 B: 1-x3+x2=-3+56 C: -x2-1-x3=-3+56 D: x2-1-x3=-3-56
- 方程y'(x) = x^2 - 3x + 2 的平衡点是 A: x = 1, x = 2 B: x = 3, x = 2 C: x = 3, x = 1 D: x = 3, x = 0
- 求方程组的解,取初值为(1,1,1)。[img=250x164]180333307ab8fde.jpg[/img] A: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fsolve(f,[1,1,1],optimset('Display','off')) B: x=fsolve(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1]) C: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fzero(f,[1,1,1]) D: x=fzero(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1])
- 方程 \({x^3} + 3{x^2} - 1 = 0\) 在 \((0,1)\) 内有一个实根 .
- 下列函数中,( )不是方程\( xy' + y - x^2 = 0 \)的解。 A: \( y = { { {x^2}} \over 3} + {1 \over x} \) B: \( y = { { {x^2}} \over 3} \) C: \( y = { { {x^2}} \over 3} + 2 \) D: \( y = { { {x^2}} \over 3} - {1 \over x} \)